ADVERTISING INTENSITY, GOOD CORPORATE GOVERNANCE, DAN PENGHINDARAN PAJAK PERUSAHAAN - Yossi Septriani; Rafif Zikrillah; Fitra Oliyan (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This research aims to examine the influence of advertising intensity and corporate governance on corporate tax avoidance. This research also tests the moderating influence of corporate governance on the relationship between advertising intensity and corporate tax avoidance. The sample used was all non-financial sector companies listed on the Indonesia Stock Exchange in the 2015–2021 period. The sampling technique used was purposive sampling, so a total of 67 companies were observed. The analysis used is panel data analysis using Stata 14 software. The results of this study show that advertising intensity has a positive effect on tax avoidance, but the proportion of independen commissioners, the proportion of female commissioners, and the moderation of the board of commissioners have no effect on tax avoidance. This research also found that there was a moderating influence from the governance element, namely board diversity, which was proxied by a female board of commissioners, which was proven to weaken the positive relationship between advertising intensity and tax avoidance. The results of this research can be used as input by the Directorate General of Taxes for evaluating improvements to company tax regulations as well as by the Komite Nasional Kebijakan Governance as material for improving regulations and implementation to create a better corporate governance system in Indonesia.